Superhydrophobic materials used for anti-icing Theory, application, and development - Hua He (Elsevier, 2021)
Summary: The accumulation of ice will reduce the performance of the base material and lead to all kinds of damage, even a threat to people's life safety. Recent increasing studies suggest that superhydrophobic surfaces (SHSs) originating from nature can remove impacting and condensing droplets from the surface before freezing to subzero temperatures, and it can be seen that hydrophobic/SH coating has good freezing cold resistance. But such anti-icing performances and developments in practical applications are restricted by various factors. In this paper, the mechanism and process of surface icing phenomenon are introduced, as well as how to prevent surface icing on SHS. The development of SH materials in the aspect of anti-icing in recent years is described, and the existing problems in the aspect of anti-icing are analyzed, hoping to provide new research ideas and methods for the research of anti-icing materials.